La participación de la familia en el rendimiento académico de los estudiantes de los octavos años de educación básica, paralelos “a”, “b”, “c” y “d”, de la matriz del colegio experimental universitario “Manuel Cabrera Lozano”, anexo al área de la Educación, el Arte y la Comunicación de la Universidad Nacional De Loja. Período lectivo 2012 – 2013 - Poma Flores, Zoila Katherine (2014)
The present investigation on: THE PARTICIPATION OF THE FAMILY IN THE ACADEMIC YIELD OF THE STUDENTS THE EIGHTH YEARS OLD, PARALLEL "TO", "B", "C" AND "D", OF THE WOMB OF THE EXPERIMENTAL UNIVERSITY SCHOOL "MANUEL GOATHERD LOZANO", ANNEX TO THE AREA OF THE EDUCATION, THE ART AND THE COMMUNICATION OF THE NATIONAL UNIVERSITY DE LOJA. PERIOD LECTIVO 2012-2013, he/she has as general objective to make aware the parents and representatives about the importance of the participation of the family in the academic yield of their children or represented. This investigation is of descriptive type. The methods that were used in this investigative work were: the deductive, analytic synthetic scientific, inductive method and the descriptive method. The used technique was the survey, the used instrument the questionnaire; and, the registration of qualifications provided by secretary of the facility. The procedure carried out in the investigation, went to request authorization to Sr. Rector to apply the instruments for the field study. Of the obtained results, to inclination the survey is verified: 73,1% comes from a nuclear family. 24,3% fulfills all the functions of the family. The 37.3%, they consider that the academic ability is the factor that more it influences in its academic yield. 81,3%, it considers that the family impacts in the academic yield. The academic highest yield corresponds Eighth "B", with an arithmetic stocking of 8,30 with a standard deviation of 063. The academic lowest yield corresponds Eighth "C", with an arithmetic stocking of 7,93 with a standard deviation of 076. Existing a very significant relationship among the participation of the family in the academic yield of the students with a relationship of 71,3% to 81,3%. The investigated population the 250 students and parents or representatives that correspond to the total of the students of the eighth year of the investigated facility constitute. After having analyzed and proven the objectives you reached the following conclusions: in the related to the variable family, it is determined that most of students belong to the type of nuclear family. With regard to the academic variable yield, he/she settles down that the highest corresponds Eighth "B" and the lowest corresponds Eighth "C." Regarding the two variables he/she was proven that an incidence of the participation of the family exists in the academic yield reached by the investigated students.